2022
DOI: 10.3390/foods11203258
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on the Use of Extracts from Medicinal and Aromatic Plants to Improve Nutritional Value and Oxidative Stability of Vegetable Oils

Abstract: Oil oxidation is the main factor limiting vegetable oils’ quality during storage, as it leads to the deterioration of oil’s nutritional quality and gives rise to disagreeable flavors. These changes make fat-containing foods less acceptable to consumers. To deal with this problem and to meet consumer demand for natural foods, vegetable oil fabricators and the food industry are looking for alternatives to synthetic antioxidants to protect oils from oxidation. In this context, natural antioxidant compounds extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 221 publications
0
8
0
Order By: Relevance
“…Pressure and temperature damage the plant cell walls, making bioactive chemicals more easily extracted. Temperature, frequency, duration, type, and volume of solvents, moisture content, and particle size of plant material all have an important impact on the extraction of bioactive compounds [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Pressure and temperature damage the plant cell walls, making bioactive chemicals more easily extracted. Temperature, frequency, duration, type, and volume of solvents, moisture content, and particle size of plant material all have an important impact on the extraction of bioactive compounds [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the fatty acid profile of oil can affect its vulnerability to oxidation and deterioration reactions. Polyunsaturated fatty acids (PUFA) such as linoleic acid (C18:2) and linolenic acid (C18:3) are much more prone to oxidation than monounsaturated (MUFA) oleic acid (C18:1) and saturated (SFA) stearic acid (C18:0) [ 3 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic antioxidants such as butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), and tertbutylhydroquinone (TBHQ) have health risks [10,12]. Terefore, strong antioxidants with fewer side efects are necessary in the food industry [11].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants are rich sources of natural antioxidants. Several studies reported the enrichment of oils with antioxidants from medicinal and aromatic plants [10,[12][13][14][15][16][17]. Yarrow (Achillea millefolium) belongs to the Asteraceae family, is one of the most famous and oldest medicinal plants that has been widely used in traditional medicine [18].…”
Section: Introductionmentioning
confidence: 99%